Pengaruh Dewan Komisaris, Komposisi Dewan Komisaris Independen, Dewan Pengawas Syariah, Frekuensi Rapat Dewan Komisaris Syariah, Dan Frekuensi Rapat Komite Audit Terhadap Pengungkapan Indeks Islamic Social Reporting Pada Bank Umum Syariah Periode 2010-2014 - Wardatul Baidok; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This study aims to find out the simultaneous and partial influences of aboard of commissioner, the composition of board of independent commissioner, board of syariah controller, the frequency of board of syariah controller meetings, and the frequency of audit committee meetings toward the disclosure of ISR index to Islamic public banks during period 2010-2014.This study uses quantitative approach, and the data is a secondary data which was obtained using purposive sampling. The data was analyzed using panel data regression. The population includes all Islamic public banks in Indonesia by focusing on period 2010-2014.The result shows that, simultaneously, the five variables have significant influence toward ISR. Partially, KDKI, DPS, and the FRDPS have significant influence toward ISR, while DK and FRKA have insignificant influence toward ISR.